Pembentukan Karakter Siswa Melalui Pembiasaan dan Keteladanan di SMP N 2 Sultan Daulat Kota Subulussalam - Saidiman Saidiman; Warul Walidin; Masbur Masbur (Tadabbur: Jurnal Peradaban Islam, 2023)
The formation of student character is important in the world of education to create a generation of quality and positive values. One approach used in the formation of student character is through habituation and exemplary. This study aims to examine the process of character building for SMP N 2 Sultan Daulat students through habituation and example. The method used in this research is qualitative research with a case study approach. Data were collected through observation, interviews and documentation studies. The research informants were teachers and students at SMP N 2 Sultan Daulat. The results of the study show that habituation and exemplary play a significant role in the formation of student character. Teachers at SMP N 2 Sultan Daulat consistently apply positive habits in their daily activities at school. They set a good example and teach students moral and ethical values. The teacher's example inspires students to internalize these values in their daily behavior.